T2-High Endotype and Response to Biological Treatments in Patients with Bronchiectasis - Martina Oriano; Andrea Gramegna; Francesco Amati; Alice D’Adda; Michele Gaffuri; Marco Contoli; Francesco Bindo; Edoardo Simonetta; Carlotta Di Francesco; Martina Santambrogio; Giovanni Sotgiu; Francesco Blasi; et al. (Biomedicines, 2021)
Although bronchiectasis pathophysiology has been historically understood around the presence of airway neutrophilic inflammation, recent experiences are consistent with the identification of a type 2 inflammation (T2) high endotype in bronchiectasis. In order to evaluate prevalence and clinical characteristics of bronchiectasis patients with a T2-high endotype and explore their response to biologicals, two studies were carried out. In a cross-sectional study, bronchiectasis adults without asthma underwent clinical, radiological, and microbiological assessment, along with blood eosinophils and oral fractional exhaled nitric oxide (FeNO) evaluation, during stable state. Prevalence and characteristics of patients with a T2- high endotype (defined by the presence of either eosinophils blood count ≥300 cells·µL−1 or oral FeNO ≥ 25 dpp) were reported. A case series of severe asthmatic patients with concomitant bronchiectasis treated with either mepolizumab or benralizumab was evaluated, and patients’ clinical data pre- and post-treatment were analyzed up to 2 years of follow up. Among bronchiectasis patients without asthma enrolled in the cross-sectional study, a T2-high endotype was present in 31% of them. These patients exhibited a more severe disease, high dyspnea severity, low respiratory function, and high impact on quality of life. Among the five patients with severe eosinophilic asthma and concomitant bronchiectasis included in the series, treatment with either mepolizumab or benralizumab significantly reduced the exacerbation rate with an effect that persists for up to 2 years of follow up. If validated across different settings, our data suggest the need to design randomized controlled trials on biological treatments targeting the T2-high endotype in bronchiectasis patients.